2014
DOI: 10.14723/tmrsj.39.161
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Zinc Oxide Nanostructures by Mist Chemical Vapor Deposition

Abstract: ZnO nanostructures with well-controlled growth on silicon substrate were fabricated in a reducing gas ambient following by a novel mist chemical vapor deposition (Mist CVD) treatment. The effects of Mist CVD post-treatment time on the crystal growth, structural properties were investigated. It was found that the morphology of ZnO nanostructures was significantly modified and regrown during Mist CVD post-treatment process. The crystallinity of ZnO nanostructures was remarkably changed after Mist CVD post-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Based on our previous study, DSSCs with a high PCE could be achieved by controlling the vertical alignment of ZnO nanorods and the quality of transparent conductive substrates [29][30][31]. In addition, mist chemical vapor deposition (mist CVD) has been proven to be an effective method for modifying ZnO nanorods [32,33]. In this study, ZnO nanorods with vertical alignment were fabricated by a multi-annealing process in reducing ambient.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study, DSSCs with a high PCE could be achieved by controlling the vertical alignment of ZnO nanorods and the quality of transparent conductive substrates [29][30][31]. In addition, mist chemical vapor deposition (mist CVD) has been proven to be an effective method for modifying ZnO nanorods [32,33]. In this study, ZnO nanorods with vertical alignment were fabricated by a multi-annealing process in reducing ambient.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still issues regarding the controlling of surface morphology, growth direction and the cost [31][32][33]. It was reported that mist CVD had advantages on the film deposition such as high uniformity, high reproducibility, simplicity, easy to control, and low cost [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate pure anatase phase TiO 2 film with high thermal stability, it is necessary to develop a novel synthesis method. In our previous research, we used a novel mist chemical vapor deposition method (mist CVD) to synthesize zinc oxide films [ 27 ]. Compared with other reported methods, even several publications using similar mist droplets source supply stage [ 28 , 29 ], this novel mist CVD had advantages in terms of precise growth controllability and large area deposition, as well as low cost and simplicity [ 27 , 30 ], and can be expected to be an alternate method to synthesize TiO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%